Nutritional practices of public elementary school pupils and teachers in Pateros - Mora, Sophia S.; Moreno, Keena S.; Nabong, Earl Bradley A.; Orilla, Kharissa Anne P.; Poltic, Faith Nester; Reyes, Jazzel Joy G.; Olea, Kert Howard S.
There is a growing public health concern of increasing rates of childhood obesity and this is 30% higher in developing countries like the Philippines (PHRD,2015). Eating habits are founded on adequate knowledge and positive nutritional attitude. Upon entry into school, the nutritional practices of children become highly influenced by environmental factors including their teachers (Williams and Mummery, 2015). However, little is known about pupils’ practices and the role of teachers in addressing gaps in their nutritional knowledge, attitudes, and practices. The study aims to determine the nutritional practices of school children and the factors that may influence this. Specifically, the objectives were (1) to describe the nutritional practices of public elementary school pupils and teachers; (2) to compare the nutritional knowledge, attitude, and practices with teachers; and (3) to determine the factors affecting nutritional practices of pupils.